The influence of strength training on overhead throwing velocity of elite water polo players - Bloomfield, J.; Blanksby, B. A.; Ackland, T. R.; Allison, G. T. (Australian Journal of Science and Medicine in Sport, 1990)
The relationship between muscular strength and morphology with overhead throwing velocity was examined in elite water polo players (N = 21). A strength training and no-training control group were formed. The authors explained the results this way: "It is more likely that this homogeneous group of elite water polo players already possessed optimum levels of upper body strength . . . and that diminished strength returns were gained from the extra training. More substantial strength gains would have been expected from players of lower calibre with poorer overall physiques." (p. 67) Implication: The study really shows strength training on unrelated activities does not improve speed actions. Strength training had no carry over to the skill tested because it was neither neuromuscularly specific nor modality specific.